PENINGKATAN MANAJEMEN KONSTRUKSI MELALUI INTEGRASI DIGITAL TECHNOLOGY:A LITERATURE REVIEW - Paulina Purba, Anggie Ria; Safura, Ferenia; Saputra, Pungky Dharma (Construction and Material Journal, 2025)
The construction industry is undergoing a major transformation with the introduction of digital technologies and the emergence of more complex risk management systems. The aim of this study is to identify the latest developments in construction management based on a review of recent literature. The method used was a systematic approach to literature published in scientific journals and international conferences, focusing on topics such as digital transformation, risk management in construction projects, and sustainability. The results indicate that the implementation of technologies such as Building Information Modeling (BIM), the Internet of Things (IoT), and Artificial Intelligence (AI) is increasing, supporting efficiency and more accurate decision-making. Furthermore, sustainability has become a key focus in modern construction projects, with the adoption of environmentally friendly materials and sustainable building practices. This study provides valuable insights for academics and practitioners in adopting innovations and improving efficiency in construction project management.